(untitled) (New York, N.Y., 2013)
Uses text and computer-generated artworks to provide detailed, realistic explorations of a wide range of topics in six broad categories. Includes glossary.
Keywords: Bách khoa toàn thư và từ điển,Encyclopedias and dictionaries